SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT PHYTOPHTHORA PADA TANAMAN MERICA DENGAN METODE CERTAINTY FACTOR: A WEB-BASED EXPERT SYSTEM FOR DIAGNOSING PHYTOPHTHORA DISEASE IN PEPPER PLANTS USING THE CERTAINTY FACTOR METHOD - Rayhana Bahar; Lilis Nur Hayati; Sugiarti Sugiarti (LPPM Universitas Abdurrab, 2026)
Phytophthora sp., is a soilborne pathogen that poses a major threat to the productivity of pepper (Piper nigrum L.) in Indonesia, with estimated yield losses reaching 10–30% in heavily infected plantations. This study designs and implements a web-based expert system using the Certainty Factor (CF) method to diagnose four clinical manifestations of Phytophthora sp. in pepper plants, comprising Stem Base Rot, Root Rot, Leaf Rot, and Fruit Rot. The knowledge base was constructed through structured interviews with a certified plant pathology expert and primary literature review, encompassing 15 clinical symptoms with 38 validated expert CF value pairs. Case study testing yielded the highest CF value for P01 (Stem Base Rot) at 1.0000 (100%), followed by P02 (Root Rot) at 0.9338 (93.38%). Functional validation through Black Box Testing confirmed all system modules operate in accordance with defined requirement specifications. The novelty of this study lies in three aspects: exclusive coverage of four Phytophthora sp. clinical manifestations in pepper within a single platform, integration of user confidence values as dynamic variables in CF computation, and direct presentation of treatment recommendations alongside the corresponding certainty percentage.